Equity in university education. An exploratory study regarding the approach to inclusive practices at the university - Walsh Payacán, Andrés (Relatos Journal, 2024)
In Chile, there is an educational policy that provides guidelines on equity in higher education. However, it is unknown whether universities have management mechanisms that ensure inclusive education that achieves equity for all participating agents. The purpose of this research was to characterize the inclusive education and diversity management model used in higher education. Through an ethnographic investigation of 1 year of nursing, occupational therapy, kinesiology and the analysis of interviews with 3 teachers and 3 directors of the Universidad de las Américas UDLA; It was determined that there are daily practices that favor the development of a culture of inclusive education and a favorable management model for students’ access and permanence in higher education. In addition, coherence is established between laws assigned by the state and the particular reality of UDLA manifested in the document Support protocol for people with disabilities (2018).